ILLOCUTIONARY FORCE IN @UDARIO.ID INSTAGRAM CONTENT PROMOTION - Triana, Herlin; Mufrihah, Mazayatul; Syukri, Haris; Haron, Rohaidah Binti; Indriyani, Vivi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
The use of Instagram social media as a promotional medium is not only built based on marketing strategies, but it requires language distinctiveness and strong linguistic power to attract Instagram users. This study examines the marketing strategies and types of illocutionary speech acts used on the Instagram account @udario.id. The method used in this study is descriptive-qualitative. The speech acts found in @udario.id content are (1) Assertive functions to conclude, report, and express; (2) Directive speech acts function to ask, command, and inquire; (3) Expressive speech acts function to complain, blame, thank; and (4) Commissive speech acts serve to promise. The most frequent Speech Acts are illocutionary directives of asking and commanding. By employing directive phrases, creators can significantly enhance engagement and visibility, as these prompts invite followers to interact with the content. When delivered in the local language, these directives become more relatable and understandable, strengthening the connection with the audience and increasing the likelihood of a response. Additionally, such prompts encourage followers to actively participate, fostering a sense of community.